The Dynamics of Exchange Rate and Stock Return Before and After the Fed Policy Normalization: Evidence from Fragile Five Countries - Arsya Javidiar; Irwan Adi Ekaputra (Sekolah Tinggi Manajemen IPMI, 2019)
Abstract: This research aims to examine the correlation between exchange rate and stock price return in each fragile five countries; Indonesia, Brazil, India, Turkey and South Africa. Using daily data, we investigate and then divide it into two periods; before Fed funds rate normalization (2013-2015) and after normalization (2016-2018), to find out whether the Fed funds rate hike caused a difference in the correlation between the two variables in each fragile five country. The methods used for this analysis are granger causality test and Vector Autoregression (VAR) using Eviews 9 program. Further investigation by analyzing the Dynamic Conditional Correlation-Multivariate GARCH (DCC MGARCH) method using Stata 15 program, which aims to find out the dynamic correlation between stock markets and also between currencies in fragile five countries. Granger test results found a difference in the relationship between variable exchange rates and stock price returns in Indonesia, India, and Turkey after the Fed normalization. Additionally, we learn that exchange rate lead stock price return in these three countries. Furthermore, the results of the DCC MGARCH test show that there is a significant positive dynamic correlation on the stock price index returns between markets. Moreover, we found similar results in testing positive and significant dynamic correlations between the exchange rates of each country. Key words: fragile five, exchange rate, stock return, VAR, DCC MGARCH